2012
DOI: 10.1175/jcli-d-11-00387.1
|View full text |Cite
|
Sign up to set email alerts
|

Causal Discovery for Climate Research Using Graphical Models

Abstract: Causal discovery seeks to recover cause–effect relationships from statistical data using graphical models. One goal of this paper is to provide an accessible introduction to causal discovery methods for climate scientists, with a focus on constraint-based structure learning. Second, in a detailed case study constraint-based structure learning is applied to derive hypotheses of causal relationships between four prominent modes of atmospheric low-frequency variability in boreal winter including the Western Pacif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
106
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 147 publications
(106 citation statements)
references
References 47 publications
0
106
0
Order By: Relevance
“…We recently introduced a very different type of climate network based on causal discovery theory [Ebert-Uphoff and Deng, 2010, 2012a, 2012b. Hlinka et al…”
Section: Climate Network Based On Causal Discoverymentioning
confidence: 99%
See 2 more Smart Citations
“…We recently introduced a very different type of climate network based on causal discovery theory [Ebert-Uphoff and Deng, 2010, 2012a, 2012b. Hlinka et al…”
Section: Climate Network Based On Causal Discoverymentioning
confidence: 99%
“…We recently introduced a very different type of climate network based on causal discovery theory [Ebert-Uphoff and Deng, 2010, 2012a, 2012b. Hlinka et al [2013] also explore causal-discovery-based methods for climate networks, contrasting methods based on Granger causality and on transfer entropy [Runge et al, 2012].…”
Section: Climate Network Based On Causal Discoverymentioning
confidence: 99%
See 1 more Smart Citation
“…This motivates the use of more sophisticated measures, known also as causality analysis methods. Indeed, it has been recently suggested that data-driven detection of climate causality networks could be used for deriving hypotheses about causal relationships between prominent modes of atmospheric variability [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…Here, we first disentangle the contributions of AMOC and sea-ice variability to GMT variations in unperturbed control runs of the CMIP5 model ensemble using graph-theoretical statistical models (Runge et al, 2012a;Ebert-Uphoff and Deng, 2012, denoted graphical models hereafter) and commonality analysis (). We relate AMOC variability to North Atlantic deep-ocean temperature and salinity and investigate an internal advective feedback mechanism.…”
Section: Introductionmentioning
confidence: 99%